Analisis Perbandingan Enkripsi dan Dekripsi Menggunakan Algoritma Simetris AES dan Hybrid (AES + RSA) Pada File Video - Alam Fahlevi Pranata; Arlin Fajar Saragih; Radika Fikri; Khairiah Rahmadani; Nazwa Putri Aulia (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
This study compares the performance of video file encryption using the symmetric Advanced Encryption Standard (AES) and a hybrid scheme combining AES with Rivest–Shamir–Adleman (RSA). The research aims to evaluate efficiency and security trade-offs between the two approaches. Experimental tests were conducted on video files of different sizes, measuring encryption time, decryption time, and file size overhead. Results show that AES achieves faster processing, with average encryption time of 0.0773 seconds and decryption time of 0.1097 seconds. In contrast, the hybrid AES–RSA scheme is slower, with encryption time of 0.0854 seconds (10.4% slower) and decryption time of 0.1405 seconds (28.1% slower), due to additional RSA key operations. While AES is more efficient for real-time applications, the hybrid method provides stronger key distribution security These findings highlight the importance of selecting encryption methods based on application requirements.